Religious Moderation Between Tradition and Modernity: Mohammed Abed al-Jabri’s Critique of Arab Reason and its Implications for Islamic Education - Mutohharun Jinan; Abil Fida Muhammad Qois Al Hadi; Fahmi Ulum Al Mubarok; Istanto Istanto; Yusuf Mukhtar Taqiyyuddin (Fitrah: Journal of Islamic Education, 2026)
Religious moderation in Indonesia has been institutionally strengthened through national policy frameworks; however, persistent intolerance among students indicates a deeper epistemological problem within religious reasoning. Existing studies generally approach moderation as a normative or socio-political agenda while neglecting the structures of reasoning that shape exclusive or moderate religious orientations. This article examines religious moderation within the dialectic of tradition and modernity through Mohammed Abed al-Jabiri’s critique of Arab reason and its implications for Islamic education. This study employs a qualitative-conceptual design using a philosophical-epistemological approach. Primary sources include al-Jabiri’s Naqd al-‘Aql al-‘Arabi and related works on bayānī, ‘irfānī, and burhānī epistemologies, supported by relevant literature on religious moderation and Islamic education. The findings reveal that sustainable religious moderation requires the reconstruction of religious reasoning through burhānī rationality, which emphasizes critical, contextual, and dialogical thinking. Consequently, Islamic education must transform its curriculum and pedagogy to cultivate critical-moderate reasoning grounded in ethical and intellectual responsibility.